New species and records of Anacroneuria (Plecoptera: Perlidae) from Rio de Janeiro State, Brazil - Baldin, Carolina; Bispo, Pitágoras Da Conceição; Novaes, Marcos Carneiro (Zootaxa, 2013)
Six species of Anacroneuria are recorded from Parque Nacional do Itatiaia and Bacia do Rio Macaé, Rio de Janeiro State, Brazil including the description of a new species, A. itatiaiensis. Anacroneuria debilis (Pictet) is redescribed from newly collected specimens. Comments on other Anacroneuria species from Rio de Janeiro State, Brazil are also presented.